Need and Access to Health Care for the Elderly in Countryside Samut Songkhram Province - benjanirat, Tipvarin; Panyakumphol, Jeerapa; Rojanabenjakun, Phannee; Ounprasertsuk, Jatuporn (International Journal of Psychosocial Rehabilitation, 2020)
Access to good quality healthcare services is essential in order to promote healthy living, to prevent the diseases, avoid disabilities and reduce the death rate. Access to healthcare revolves around the idea that the healthcare services are being provided in order to get the positive outcomes related to health. Interaction quality with the health care providers is an essential component of the overall situation of health care. Therefore, the current study has been conducted with the aim to explore the impact of interaction quality with healthcare providers on the access to healthcare and need of healthcare in Samut Songkhram province along with the mediating role of value of healthcare. In the continuation of this purpose, the researcher has collected data from the people who have experienced the health care system of the research area. After the careful analysis of the collected data, the results have been obtained. These results have made it clear that interaction quality with healthcare providers has significant and positive impact on access to healthcare and needs of healthcare. Moreover, these results have also made it evident that the mediating role of value of healthcare is also significant in the relationship between interaction quality, and access and needs of healthcare.